4x(x+6)-x elevado a 2 =5x elevado a 2
Soluções para a tarefa
Respondido por
3
4x² +24x - x² = 5x²
4x² + 24x - x² - 5x² =0
4x² - x² - 5x² + 24x = 0
- 2x² +24x = 0 (-1)
2x² - 24x = 0
fatoração em fator comum:
2x(x - 12)
Fazer cada termo separadamente:
2x = 0 x= 0/2 x=0
x - 12 =0 x = 12
4x² + 24x - x² - 5x² =0
4x² - x² - 5x² + 24x = 0
- 2x² +24x = 0 (-1)
2x² - 24x = 0
fatoração em fator comum:
2x(x - 12)
Fazer cada termo separadamente:
2x = 0 x= 0/2 x=0
x - 12 =0 x = 12
Perguntas interessantes
Sociologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás
Música,
1 ano atrás
Matemática,
1 ano atrás